Nosocomial Infections among Pediatric Patients with Neoplastic Diseases - Peninnah Oberdorfer; Natthida Pongwilairat; Charles H. Washington (Hindawi Limited, 2009)
Background. Pediatric patients with neoplastic diseases are more likely to develop nosocomial infections (NIs). NIs may prolong their hospital stay, and increase morbidity and mortality. Objectives. The objectives of this study were to determine: (1) the incidence of NIs, (2) sites of NIs, (3) causal organisms, and (4) outcomes of NIs among pediatric patients with neoplastic diseases. Methods. This study was a prospective cohort study of pediatric patients with neoplastic diseases who were admitted to the Chiang Mai University Hospital, Thailand. Results. A total of 707 pediatric patients with neoplastic diseases were admitted. Forty-six episodes of NIs in 30 patients were reported (6.5 NIs/100 admission episodes and 7 NIs/1000 days of hospitalization). Patients with acute lymphoblastic leukemia had the highest number of NIs (41.3%). The most common causal organisms were gram-negative bacteria (47.1%). Patients who had undergone invasive procedures were more likely to develop NIs than those who had not (P<.05). The mortality rate of patients with NIs was 19.6%. Conclusion. Pediatric patients with neoplastic diseases are more likely to develop NIs after having undergone invasive procedures. Pediatricians should be aware of this and strictly follow infection control guidelines in order to reduce morbidity and mortality rates related to NIs.